A study of independent middle class women: accommodation crisis, living experiences & negotiation strategies in Dhaka - Aisharja, Tasnim Rahman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.